2015
DOI: 10.17848/wp15-231
|View full text |Cite
|
Sign up to set email alerts
|

Who Believes in Me? The Effect of Student-Teacher Demographic Match on Teacher Expectations

Abstract: Teachers are an important source of information for traditionally disadvantaged students. However, little is known about how teachers form expectations and whether they are systematically biased. We investigate whether student-teacher demographic mismatch affects high school teachers' expectations for students' educational attainment. Using a student fixed effects strategy that exploits expectations data from two teachers per student, we find that nonblack teachers of black students have significantly lower ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…One explanation is that teachers exercise discretion in student referral, diagnosis, or selection along racial/ethnic lines in ways that contribute to patterns of disproportionality in assignment. Teachers may perceive potential giftedness differently in students from other-race groups because of differences in backgrounds or biases in their judgments or expectations (Gershenson, Holt, & Papageorge, 2015; Grissom et al, 2015). Alternatively, students may perform or behave differently in the presence of an own-race teacher in ways that make giftedness easier to identify, or students or parents may engage differently in the gifted assignment process itself in the presence of own-race teachers (Grissom et al, 2015; Lim, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that teachers exercise discretion in student referral, diagnosis, or selection along racial/ethnic lines in ways that contribute to patterns of disproportionality in assignment. Teachers may perceive potential giftedness differently in students from other-race groups because of differences in backgrounds or biases in their judgments or expectations (Gershenson, Holt, & Papageorge, 2015; Grissom et al, 2015). Alternatively, students may perform or behave differently in the presence of an own-race teacher in ways that make giftedness easier to identify, or students or parents may engage differently in the gifted assignment process itself in the presence of own-race teachers (Grissom et al, 2015; Lim, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The expectations teachers have for their Black students may vary, however, based on the race of the teacher. For example, Gershenson et al (2016) found that non-Black teachers of 10th grade Black students in a representative sample of U.S. schools had significantly lower educational expectations for the students than Black teachers, and this effect was particularly strong when considering Black male students. Lewis and Diamond (2015) also found that many White parents assumed that Black parents valued education less, and White parents believed that these purported differences explained racial inequality in the school setting.…”
Section: Race and Disciplinementioning
confidence: 99%
“…That is, researchers have demonstrated educators are more likely to perceive European American students as “gifted” than student of color, when all other characteristics are identical (Elhoweris et al, 2005). Teachers may also hold different beliefs about what giftedness is in students from races other than their own because of varying backgrounds or biases in their judgments or expectations (Gershenson et al, 2015; Grissom et al, 2015; Grissom & Redding, 2016). Therefore, it is critical to not only understand those who “monitor the gate,” it is equally important to support and promote those who fall “outside the gate” (Collyer et al, 2017, p. 97).…”
Section: Gatekeeping In the Academic Domainsmentioning
confidence: 99%